Experiments on cyclic behaviour of cold-formed steel-rubberised concrete semi-rigid moment-resisting connections. (15th November 2022) - Bagheri Sabbagh, Alireza; Jafarifar, Naeimeh; Davidson, Paul; Ibrahimov, Kanan
Highlights: Bare steel and composite semi-rigid moment-resisting connections were tested. The connections comprised CFS tubular sections connected using side plates. Various failure limit states were captured through the tested connections. The infill concrete effectively prevented beam local buckling. Side plate plasticity considered as a desirable energy dissipation mechanism. Abstract: This paper presents the results of full-scale physical tests on a recently developed cold-formed steel (CFS) semi-rigid moment-resisting connection infilled with rubberised concrete (RuC) for seismic application. The connection comprises side-plates attached to both sides of built-up tubular CFS beam and column sections through either screwed or welded connections. The tests were performed on both bare steel and CFS-RuC composite connections under cyclic loading for comparison purposes. The predominant modes of failure are beam local buckling and side plate plasticity in the bare steel connections and screw shear failure in the composite connections. The results show that the composite connection typically reaches 45% higher strength and 21% greater energy dissipation capacity than the bare steel connection both having 24 screw arrays. These indicate the beneficial effects of the infill RuC in prevention of the beam local buckling in connections with identical connection configuration. The energy dissipation capacity of the bare steel connection having 36 screw arrays, however, was 70% greater than that of the composite connection with 24 screw arrays. This reflects side plate plasticity being a more effective energy dissipation mechanism than the other identified mechanisms.